BIMBINGAN BELAJAR MATEMATIKA PADA SISWA SD DESA KALIDILEM LUMAJANG - SUJIWO, DIMAS ANDITHA CAHYO (UNIVERSITAS PGRI MADIUN, 2017)
AbstractTutoring is the guidance given by experts to assist individuals in facing and solving problems related to learning.The purpose of tutoring is directing students to his potential optimally. In the process of learning activities, the teacher’s task is to guide students to find various potentials. Tutoring is provided to students of class VI Kalidilem Village Lumajang. the difficulty and cost of an obstacle course for most students. The objective of this activity is to assist students in improving students’ motivation to learn mathematics. Topics studied in this activity is area of plane. The method used in this study guidance activities is a method of assisted props discussion.The number of students in tutoring activities is 8 students.Students were very enthusiastic tutoring activities. Based on the results of activities states that students who obtain a score above 75 is 7 students of 8 students or the percentage of student learning outcomes was 87.5%.Results tutoring activities show that all students are very pleased with the activities of tutoring. Discussion method props aided greatly assist students in understanding the plane. AbstrakBimbingan belajar adalah bimbingan yang diberikan oleh tenaga ahli untuk membantu individu dalam menghadapi dan memecahkan permasalahan yang berkaitan dengan belajar. Tujuan bimbingan belajar ini adalah mengarahkan siswa yang sesuai dengan potensinya secara optimal. Dalam proses kegiatan pembelajaran, tugas guru adalah membimbing siswa agar dapat menemukan berbagai potensi yang dimilikinya. Bimbingan belajar ini diberikan kepada siswa kelas VI Desa Kalidilem Lumajang. Kesulitan dan biaya kursus menjadi kendala bagi sebagian besar siswa. Tujuan diadakannya kegiatan ini adalah untuk membantu siswa dalam meningkatkan motivasi belajar matematika siswa. Topik yang dipelajari dalam kegiatan ini adalah luas bangun datar. Metode yang digunakan paga kegiatan bimbingan belajar ini adalah metode diskusi berbantuan alat peraga. Jumlah siswa dalam kegiatan bimbingan belajar adalah 8 siswa. Siswa sangat antusias mengikuti kegiatan bimbingan belajar. Berdasarkan hasil kegiatan menyatakan bahwa siswa yang memperoleh skor di atas 75 adalah 7 siswa dari 8 siswa atau prosentase hasil belajar siswa adalah 87,5%. Hasil kegiatan bimbingan belajar menunjukkan bahwa seluruh siswa sangat senang dengan kegiatan bimbingan belajar. Metode diskusi berbantuan alat peraga sangat membantu siswa dalam memahami bangun datar.